Корекція інсуфляцією киснем, субстанцією "КД-234" та реамберином гострого респіраторного дистрес-синдрому у щурів: ефективність комбінованої дії = Correction of acute respiratory distress syndrome in rats by the insufflation of oxygen substance "KD-234" and Reamberin: efficacy of combined actions - Samwel Savchuk; Oleksandr Oliynyk; Lubov Tsaryk (Kazimierz Wielki University, 2016)
Savchuk Samwel, Oliynyk Oleksandr, Tsaryk Lubov. Корекція інсуфляцією киснем, субстанцією "КД-234" та реамберином гострого респіраторного дистрес-синдрому у щурів: ефективність комбінованої дії = Correction of acute respiratory distress syndrome in rats by the insufflation of oxygen substance "KD-234" and Reamberin: efficacy of combined actions. Journal of Education, Health and Sport. 2016;6(7):195-206. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57323 http://ojs.ukw.edu.pl/index.php/johs/article/view/3673       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.06.2016. Revised 09.07.2016. Accepted: 09.07.2016.     Корекція інсуфляцією киснем, субстанцією "КД-234" та реамберином гострого респіраторного дистрес-синдрому у щурів: ефективність комбінованої дії Correction of acute respiratory distress syndrome in rats by the insufflation of oxygen substance "KD-234" and Reamberin: efficacy of combined actions   Самвел Савчук, Олександр Олійник, Любов Царик Samwel Savchuk, Oleksandr Oliynyk, Lubov Tsaryk   Тернопільський державний медичний університет ІМ. І.Я. Горбачевського I. Horbachevsky Ternopil State Medical University                        Резюме. У статті наведено результати дослідження ефективності впливу інсуфляції кисню, похідного ксантину - солі 3-(8-бромо-1,3-диметил-2,6-діоксо-2,3-дигідро-1Н-пурин-7(6Н)-іл)пропаноату (субстанції «КД-234») і  реамберину шляхом вивчення динаміки продуктів  пероксидного окиснення ліпідів та антиоксидантного захисту в умовах експериментального гострого респіраторного дистрес-синдрому.               Встановлено істотний позитивний вплив на пероксидне окиснення ліпідів комбінації інсуфляції кисню із похідним ксантину (зменшення ТБК-АП у ССГ-тварин - на 38,8 %, у НСГ-тварин - на 60,9 % (р<0,05)) та з реамберином (зниження ТБК-АП у ССГ-тварин - на 24,4 %, у НСГ-тварин - на 54,9 % (р<0,05)) порівняно з монотерапією. При цьому найкращий антирадикальний ефект у групі тварин з ГРДС відмічено при комбінованому застосуванні інсуфляції кисню із похідним ксантину. Поєднане застосування інсуфляції киснем і субстанції «КД-234» в умовах експериментального гострого респіраторного дистрес-синдрому має схожий влив на ферментну ланку антиоксидантної системи як за умови корекції інсуфляцією киснем, проте значно підвищує антиоксидантно-прооксидантний індекс тканини печінки (р<0,05), тоді як комбінація інсуфляції кисню із реамберином не має значимого впливу як на ферментну, так і неферментну ланки системи антиоксидантного захисту.                   Abstract. The article is showed the results of the effectiveness of insufflation of oxygen xanthine derivative salt (Substance "KD-234") and Reamberin according to the studies of the lipid peroxidation and antioxidant protection products dynamics in experimental acute respiratory distress symptoms.               It was established a significant positive effect of oxygen insufflation with xanthine derivatives with Reamberin combination on lipid peroxidation (reduction of MDA (p <0.05)) compared to monotherapy. It was the gratest antiradical effect in the group of animals with ARDS during the combined use of oxygen insufflation xanthine derivative. The combined use of oxygen insufflation and substance "KD-234" in the conditions of experimental acute respiratory distress syndrome were showed similar impact on link enzymatic antioxidant system both in terms of oxygen insufflation correction. It was significantly increased the antioxidant-prooxidant index in liver (p <0.05), while the combination of oxygen insufflation with Reamberin had a significant effect on the enzyme and nonenzyme parts of antioxidant protection.                 Ключові слова: респіраторний дистрес-синдром, похідні ксантину, реамберин, ефективність.               Keywords: acute respiratory distress syndrome, xanthine derivatives, Reamberin, efficiency.